So Much Depends Upon a Cup of Coffee: A Reader Response Analysis of Eliot’s “Sweeney among the Nightingales” - MANSUR, Visam (Journal of Ecohumanism, 2024)
T.S. Eliot’s poem “Sweeney among the Nightingales” is a short dramatic monologue that introduces Sweeney as rude and cruel character, in a setting where he interacts with several women referred to as ‘Nightingales’ in a brothel. Sweeney finds himself involved in a cunning plot in that brothel. He is seduced and given alcohol to impair his judgement. To thwart the conspiracy against him, he has to have a cup of coffee to help him remain awake. By having one of the women drop the cup of coffee, Eliot paves the way for unconventional reading of the text that focuses on the unmentioned spilled coffee in the poem. The unmentioned spilled coffee becomes more important than the cup of coffee dropped by the woman in the Spanish cape. For the absence of coffee at the end of Sweeney’s late night activities deters his sobriety; helps the conspirators to attain their goal, and further contributes to the theme(s) of the poem.